Praxishandbuch Open Access - Mittermaier, Bernhard (De Gruyter Praxishandbuch, 2017)
This book introduces open access publishing from the perspective of the author and the institution. It describes workflows and important tools while also offering a classification of various business models. While the book focuses on the publication of manuscripts, it also surveys data publishing.